Correlación entre ckmb enzimática y ckmb de masa como bioindicador específico en el diagnóstico de infarto agudo de miocardio en pacientes del hospital carlos andrade marín de la ciudad de quito en el período noviembre del 2012 a abril del 2013 - Rojas Salazar, Gabriela Valeria (2013)
Myocardial infarction is one of the most common causes of the death worldwide. It is therefore important the early fiagnosis and accurate to minimiza myocardial dell damage and institute appropriate tretment. The importance of testing CK-MB, is in the diagnosis of AMI and the dofference between the cardiac injury and skeletal muscle. Creatine Kinase-MB is considered one of the best laboratory tests for this purpose. The detection is important both for the degree of impact and the effectiveness of treatment.The porcentage of CK-MB activity over 6% is associated with acute myocardial infarction (AMI)